Coherence of oscillations in matter and supernova neutrinos - Silva, Yago Philippe Pôrto, 1992- (2021)
Abstract: We study the propagation coherence for neutrino oscillations in media with different density profiles. For each profile, we find the dependence of the coherence length, L-coh, on neutrino energy and address the issue of correspondence of results in the distance and energy-momentum representations. The key new feature in matter is existence of energy ranges with enhanced coherence around the energies E-0 of "infinite coherence" at which L-coh -> infinity. In the configuration space, the infinite coherence corresponds to equality of the (effective) group velocities of the eigenstates. In constant density medium, there is a unique E-0, which coincides with the MSW resonance energy of oscillations of mass states and is close to the MSW resonance energy of flavor states. In the case of massless neutrinos or negligible masses in a very dense medium the coherence persists continuously. In the adiabatic case, the infinite coherence is realized for periodic density change. Adiabaticity violation changes the shape factors of the wave packets (WPs) and leads to their spread. In a medium with sharp density changes (jumps), splitting of the eigenstates occurs at crossing of each jump. We study the increase of the coherence length in a single jump and periodic density jumps - castle-wall (CW) profiles. For the CW profile, there are several E-0 corresponding to parametric resonances. We outlined applications of the results for supernova neutrinos. In particular, we show that coherence between two shock wave fronts leads to observable oscillation effects, and our analysis suggests that the decoherence can be irrelevant for flavor transformations in the central parts of collapsing stars